Effect of Methyl Jasmonate on Vegetative Growth and Formation of Potato Tuber (Solanum tuberosum L. var. Granola) - Rohmawati, Triana; Dewi, Kumala (Biogenesis: Jurnal Ilmiah Biologi, 2019)
Potato (Solanum tuberosum L.) is one of the main commodities of food crops in Indonesia that are rich in vitamins, antioxidants, and carbohydrates. One of the most popular varieties of vegetable potatoes and become the leading varieties of producer farmers is Granola. Methyl jasmonate is a hormone known to modulate physiological events in plants such as encouraging tuber formation, functioning in vegetative development and fruit development. This study aims to evaluate the influence of methyl jasmonate on vegetative growth and potato tuber formation. In the fourth weeks, the methyl jasmonate applied with concentrations: 0 ppm (control), 12.5 ppm, 25 ppm, 50 ppm, 75 ppm, and 100 ppm. Measurement of plant height, number of leaves performed at the age of 4 weeks until the age of 7 weeks. The leaf area measured in seven weeks. The height of the plant measured in 4 weeks until 7 weeks. The leaf area measured in 7 weeks. Once the harvest performed, then measure the amount and weight of the tuber. Data were analyzed using ANOVA One way, if the data represent a significant difference, then continued with DMRT with an error rate of 5%. The results showed that methyl jasmonate administration generally had no effect on vegetative growth (plant height, leaf number, and leaf area) of the potato plant. The methyl jasmonate application tends to decrease the number of tubers formed but increases the size and weight of the tubers.